2007
DOI: 10.1111/j.1530-0277.2006.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of the ADHIB*3 Allele With Alcohol‐Related Phenotypes in Trinidad

Abstract: This study suggests, in this sample of Trinidadians, that the ADH1B(*)3 allele is associated with protection from the development of alcoholism but is also associated with enhanced risk for elevated serum ALT levels in those individuals who do become alcohol dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Participants were dichotomized as carriers of at least one protective, low-risk allele ( ADH1B*3 ) or non-carriers for main analyses, because modeling a cross-product gene-environment interaction using a three-category polymorphic genotype may increase false positive and false negative findings 33 and only a small number of participants in our sample (3%) carried two copies of the ADH1B*3 allele, similar to previous studies. 18,19 We note that ancillary analyses with a continuous genotype classification of the number (instead of presence) of ADH1B*3 alleles yielded the same pattern of significance of the interaction effects between ADH1B and drinking motives.…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…Participants were dichotomized as carriers of at least one protective, low-risk allele ( ADH1B*3 ) or non-carriers for main analyses, because modeling a cross-product gene-environment interaction using a three-category polymorphic genotype may increase false positive and false negative findings 33 and only a small number of participants in our sample (3%) carried two copies of the ADH1B*3 allele, similar to previous studies. 18,19 We note that ancillary analyses with a continuous genotype classification of the number (instead of presence) of ADH1B*3 alleles yielded the same pattern of significance of the interaction effects between ADH1B and drinking motives.…”
Section: Methodsmentioning
confidence: 59%
“…Further, study eligibility criteria required that all participants report alcohol consumption at least once in the past 30 days, thus the relationship between ADH1B*3 , drinking motives, and alcohol use among occasional or non-drinkers remains unknown. Given that the ADH1B*3 allele has been shown to protect against drinking among Blacks, 18,19 study eligibility criteria may have excluded potential carriers who refrain from alcohol use due to negative reactions following drinking. However, this potential bias due to exclusion of abstainers may be negligible given that the prevalence of ADH1B*3 was within Hardy-Weinberg equilibrium in our sample and matched those of other studies among Blacks (34 – 41%).…”
Section: Discussionmentioning
confidence: 99%
“…Among those participants who were alcohol dependent, ADH1B*3 was associated with significantly higher levels of the liver enzyme aspartate aminotransferase, which can be indicative of alcohol-induced liver disease. These analyses suggest that in this sample of Trinidadians, the ADH1B*3 allele has a protective effect against development of alcoholism; however, in people who do become alcohol dependent, the allele is associated with an enhanced risk for liver disease (Ehlers et al 2007).…”
Section: Frequencies Of Adh and Adh Alleles In Indo-and Afro-trinidadmentioning
confidence: 98%
“…Another analysis investigated the association of alleles of another type of ADH, ADH1B, with alcohol dependence, drinking history, and liver function in Indo-and AfroTrinidadians (Ehlers et al 2007). That study determined the frequencies of two alleles, ADH1B*2 and ADH1B*3.…”
Section: Frequencies Of Adh and Adh Alleles In Indo-and Afro-trinidadmentioning
confidence: 99%
“…There is strong evidence for a negative association between the ADH1B*2 allele (i.e., A allele at rs1229984) and alcohol dependence and alcohol consumption (Ehlers et al, 2012;Konishi et al, 2004;Li et al, 2011;Macgregor et al, 2009), as well as evidence for the ADH1B*3 allele (i.e., T allele at rs2066702) (Edenberg et al, 2006;Ehlers et al, 2007). Bierut et al (2012) reported reduced risk for alcohol dependence for the A allele at rs1229984 versus the G/G genotype in a combined sample of European Americans and African Americans.…”
mentioning
confidence: 99%